Overview of Quality in Cardiovascular Imaging and Procedures for Clinicians: Focus on Appropriate-Use-Criteria Guidelines - Stainback, Raymond F. (Methodist Debakey Cardiovasc J, 2014)
Cardiovascular imaging and procedures have experienced exponential growth over the past 20 years in terms of new modalities, procedure volume, technological sophistication, and cost. As a result, related quality improvement tools have become multifaceted works in progress. This article briefly summarizes the evolution of the time-honored American College of Cardiology Foundation/American Heart Association clinical practice guidelines versus the newer American College of Cardiology Foundation appropriate-use-criteria guidelines and how these may interact with emerging performance measures, clinical data registries, and cardiovascular laboratory accreditation initiatives.